KREATIVITAS SISWA DALAM PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PROBLEM POSING DI KELAS IX SMP KRISTEN KANAAN KUBU RAYA - Wicaksono, Raden Fajar Septiary; Hartoyo, Agung; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to determine students' creativity in mathematics learning with a problem posing approach of nine grade in Kanaan Christian Junior High School Kubu Raya. The research method used is experiment with pre-experimental form. The sample of this study was 17 students of class IX. The results of the data analysis showed that in mathematics learning with the problem posing approach, the average value of students was 84.47 in the form of pre-solution posing, 38.89 in the form of within solution posing, and 15.56 in the form of post solution posing. Overall improvement, the results of calculations using N-gain calculations, there is a significant change in student creativity after being taught with mathematics learning with a problem posing approach, namely the fluency aspect in the high category (increased by 52.15%), flexibility in the medium category (increased by 37 , 85%), and novelty in the low category (increased by 8.26%).Â Keywords : Creativity, Problem Posing, Fluency, Flexibility, novelty